The Effect of Acupuncture Therapy on Reducing Blood Pressure in Hypertension Patients: Meta-Analysis - Faricha Indra Hapsari; Setyo Sri Rahardjo; Hanung Prasetya (Journal of Epidemiology and Public Health, 2021)
Background: Acupuncture is a traditional Chinese medicine for treating ailments, including diseases of the cardiovascular system, such as hypertension. Acupuncture modulates neurohumoral regulatory systems and cardiovascular function. This study aims to estimate the effectiveness of acupuncture therapy in reducing blood pressure in hypertensive patients. Subjects and Method: This was a systematic review and meta-analysis, with PICO, namely Population= hypertension cases aged 20-80 years. Intervention= acupuncture therapy. Comparison= Sham/ Placebo/ No Treatment Acupuncture. Outcome = Blood pressure. The articles used in this study were obtained from several databases including Google Scholar, MEDLINE/ PubMed, Science Direct, Hindawi, BMC, Europe PMC and Springer Link. These articles were collected for 1 month. The keywords to search for articles were as follows: “acupuncture”, “hypertension”, “randomized controlled trial”, “hypertension randomized controlled trial”, “acupuncture randomized controlled trial”, “acupuncture for primary hypertension”, “acupuncture for hypertension essential” AND “acupuncture for blood pressure”. The articles included in this study are full text articles with a randomized controlled trial study design. Articles were collected using PRISMA flow diagrams and analyzed using the Review Manager application (RevMan) 5.3. Results: A total of 9 articles were reviewed in this meta-analysis. Articles are from Boston, Germany, Korea, China, India and Taiwan. The study showed that acupuncture therapy was able to reduce systolic blood pressure with the Standardized Mean Different by 0.54 compared to sham acupuncture /placebo/no treatment (SMD= 0.54; 95% CI= -1.04 to -0.04; p<0.05). Acupuncture reduced diastolic blood pressure 0.49 units (SMD= 0.49; 95% CI= -0.99 to 0.02; p>0.05) compared to sham acupuncture/ placebo, but it was statistically non significant. Conclusion: Acupuncture can reduce systolic blood pressure, but it is less significant in reducing diastolic blood pressure in hypertensive patients.